Detection and molecular characterization of Actinomyces denticolens causing lymph node abscessation in horses - van den Wollenberg, L.; van Maanen, C.; Buter, R.; Janszen, P.; Rey, F.; van Engelen, E. (Frontiers in Veterinary Science, 2023)
Abstract This report describes the identification and molecular characterization of Actinomyces denticolens that caused abscessation of the submandibular lymph node in three unrelated horses. PCR, culture and serology for Streptococcus equi subsp. equi yielded a negative result in all samples submitted for these cases. Bacterial culture and subsequent identification with MALDI-TOF MS resulted in a reliable identification of A. denticolens in two of the three isolates. Final confirmation of A. denticolens for all three isolates was achieved using whole genome sequencing, supported by genotyping using multi locus sequence typing (MLST). The three isolates showed 95% nucleotide sequence identity. The number of single nucleotide polymorphisms (10, 170 to 36, 058) indicated that the strains were polyclonal, suggesting that these cases were epidemiologically unrelated. Four known virulence genes were detected. The absence of known antibiotic resistance genes was in line with the high susceptibility as indicated by the susceptibility patterns obtained for two of the three isolates. We conclude that A. denticolens should be included in the differential diagnosis of (submandibular) lymph node abscessation in horses, especially if strangles cannot be confirmed with laboratory diagnostics. Furthermore we report the first draft genome of A. denticolens isolated from horses.